ICP-RIE dry etching using Cl2-based on GaN - Siti Azlina Rosli; Azlan Abdul Aziz; Md Roslan Hashim (Universiti Kebangsaan Malaysia, 2011)
In this study, the plasma characteristics and GaN etch properties of inductively coupled Cl2/Ar and Cl2/H2 plasmas were investigated. Our results showed that inductively coupled plasma (ICP) etching of gallium nitride by using Cl2/Ar and Cl2/H2 were possible to meet the requirements (anisotropy, high etch rate and high selectivity). We have investigated the etching rate dependency on the percentage of argon and hydrogen in the gas mixture and the DC voltage. Surface morphology of the etched samples was checked by SEM and AFM. It was found that the etched surface was anisotropic and the smoothness of the etched surface is comparable to that of polished wafer. As results, gas mixture using Cl2/Ar, we obtained highest etching rates; 5000 Å/min and ~0.5 nm rms roughness for n-GaN and for p-GaN, the etching rates was 3300 Å/min and ~0.7 nm for rms roughness. Meanwhile, for gas mixture using Cl2/H2, the etching was 1580 Å/min for n-GaN and 950 Å/min for p-GaN.